Analysis of the Effect of Industrial Sector Exports, Foreign Investment Industrial Sector and Inflation on Indonesia Gross Domestic Product in 1983-2017 - Baene, Christianity Winner (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study aims to determine the effect of industrial sector exports, foreign investment in the industrial sector and inflation on Indonesia Gross Domestic Product in 1983-2017. The data used are industrial sector export data, foreign investment in the industrial sector, inflation of Indonesia's economic growth in 1983-2017 with multiple linear regression analysis (OLS) methods. The analysis shows that the export of the industrial sector has a positive and significant effect on Indonesia's Gross Domestic Product, the foreign investment of the industrial sector has a negative and significant effect on Indonesia's Gross Domestic Product. Inflation has a negative and significant effect on Indonesia's Gross Domestic Product. Thus, exports from the industrial sector have a positive and significant effect on economic growth, foreign investment in the industrial sector and inflation have a negative and significant effect on Indonesia's economic growth from 1983-2017. This research suggests that the government works harder to increase industrial sector exports, reduce inflation and also continue to establish good cooperation with international trade partners. Monitor and attract foreign investment in the industrial sector so that the Indonesian industrial sector is able to compete in the midst of the development and improvement of industrial developed countries. Licensing arrangements must be made easier, so that foreign investment in the industrial sector quickly arrives in the field so as to open up new industrial land thereby absorbing labor and increasing production in the industrial sector so that it will be able to increase Indonesia's economic growth.